Experimental Investigation on Preparation and Stability of Al2O3 Nanofluid In Deionized Water and Ethylene Glycol - Wahaizad, Safiei; M. M., Rahman; M. A., Hadi; W. H., Azmi; M. N., Arifin (Akademi Baru, 2021)
Nanofluid has the potential as a cooling medium for the next generation fluid as it possesses many advantages in many engineering applications. However, one of the main challenges is to establish a well-dispersed nanoparticles system in a base fluid. The preparation technique of nanofluid plays an important part as it influences the measurement of thermal conductivity. Therefore, the objectives of this study are to evaluate the nanoparticle dispersion in different base fluid compositions and to determine the optimized suspension sonication time. In detail, 0.2 wt.% of Al2O3 nanofluid stability in the three ratios of base fluid (deionized water:ethylene glycol) 80:20, 70:30 and 60:40 were studied. The studies were based on a visual inspection and spectral absorbance analysis. It has clearly shown that the nanofluids prepared in 60:40 base fluid within 3 hours sonication time was the most stable suspension compared to other nanofluids. The visual inspection indicated nanofluid condition remains stable after 30 days. The spectral absorbance of nanofluids was recorded at 100 % for 5 days after preparation and remains above 95 % compared to the initial value, reflecting stable suspension. Hence the novelty of this work lies in the nanofluid stability based on sonication time and base fluid compositions.